2022
DOI: 10.1177/21582440221128179
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Trends and the Emerging Research Directions of Digital Tourism in the Last Three Decades: A Bibliometric Analysis

Abstract: Digital technologies have radically changed the tourism industry and gaining a lot of attention from the stakeholders. At present, there is voluminous but fragmented research to cover the various aspects of digital tourism, but a consolidated “big picture” of the extant research is missing. By performing a bibliometric analysis of 827 papers on digital tourism, an attempt has been made to fill this void. The investigation revealed that the management of smart destinations, the internet as a communication and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 89 publications
1
17
0
1
Order By: Relevance
“…Source credibility makes the advertisers use the language, context, and layout that adjust to the native advertisements (Bell et al 2021 ) to make an advertisement effective. Prior studies found that "advertisement credibility" has a significant relationship with "attitudes" and "behavioral intentions" (Kalia et al 2022b ; Tsang et al 2004 ; Zhang and Mao 2008 ). Thus, we can hypothesize that:…”
Section: Conceptual Background and Hypothesis Formulationmentioning
confidence: 99%
“…Source credibility makes the advertisers use the language, context, and layout that adjust to the native advertisements (Bell et al 2021 ) to make an advertisement effective. Prior studies found that "advertisement credibility" has a significant relationship with "attitudes" and "behavioral intentions" (Kalia et al 2022b ; Tsang et al 2004 ; Zhang and Mao 2008 ). Thus, we can hypothesize that:…”
Section: Conceptual Background and Hypothesis Formulationmentioning
confidence: 99%
“…The bibliometric analysis shows a map of tourism’s distribution of knowledge structures, measurement and evaluation in some particular topic (Robertson et al , 2020). Several studies using the bibliometric approach in the tourism topic include (Singh and Bashar, 2021) concerning e-tourism; (Suban et al , 2021) related to halal and Islam; (Sánchez et al , 2017) about wine; (Liu and Li, 2020) and (Khanra et al , 2021) related to ecotourism;, (Knani et al , 2022) about the role artificial intelligence in hospitality and tourism; (Herrera-Franco et al , 2020) about geo-tourism; and (Kalia et al , 2022) about the past three decades of digital tourism.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these studies has made a scientific contribution in looking at trends in specific topics and succeeded in providing comprehensive information. Especially from Kalia et al (2022) argued that new research areas in digital tourism include consumer behavior, technology and sustainability, management of smart destinations and the internet as a platform for marketing and communication. When Kalia et al (2022) analyzes the current direction of digital tourism research (2020), this study aims to evaluate the scientific TRC 4,1/2 structure of digital tourism based on the Scopus database (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotional efforts with digital assistance have recently received attention from various stakeholders (Kalia et al, 2022) because they are considered more effective in facilitating public access (Rtelinggi et al, 2020) with a wide reach. There are even several previous studies that discuss digital tourism branding, such as research (Moturu et al, 2020), (Van & Hieu, 2020) and (Nguyen, 2018).…”
Section: Introductionmentioning
confidence: 99%